The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1002/anie.201203556
|View full text |Cite
|
Sign up to set email alerts
|

Acceptorless Photocatalytic Dehydrogenation for Alcohol Decarbonylation and Imine Synthesis

Abstract: It has come to light: Renewed interest in conversions of highly oxygenated materials has motivated studies of the organometallic-catalyzed photocatalytic dehydrogenative decarbonylation of primary alcohols into alkanes, CO, and H(2). Methanol, ethanol, benzyl alcohol, and cyclohexanemethanol are readily decarbonylated. The photocatalysts are also active for amine dehydrogenation to give N-alkyl aldimines and H(2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(44 citation statements)
references
References 51 publications
1
43
0
Order By: Relevance
“…The IR spectrum showed a strong absorbance at 1955 cm -1 , proving that the CO ligand was still coordinated. To obtain more information, the newly observed species was labeled with [ 13 C]CO from α-[ 13 C]-benzyl alcohol, which afforded a double doublet in the 13 C NMR spectrum at 167.4 ppm and changed the two singlets in the 31 P NMR spectrum into two doublets with couplings of 3.5 and 14.3 Hz, respectively. The disappearance of the C-P trans-coupling and the P-P cis-coupling from 1, indicates that one of the phosphines has dissociated.…”
Section: The Effect Of Licl and H 2 Omentioning
confidence: 99%
“…The IR spectrum showed a strong absorbance at 1955 cm -1 , proving that the CO ligand was still coordinated. To obtain more information, the newly observed species was labeled with [ 13 C]CO from α-[ 13 C]-benzyl alcohol, which afforded a double doublet in the 13 C NMR spectrum at 167.4 ppm and changed the two singlets in the 31 P NMR spectrum into two doublets with couplings of 3.5 and 14.3 Hz, respectively. The disappearance of the C-P trans-coupling and the P-P cis-coupling from 1, indicates that one of the phosphines has dissociated.…”
Section: The Effect Of Licl and H 2 Omentioning
confidence: 99%
“…[6][7][8] For instance, Zhao et al reported the photocatalytic oxidation of aromatic amines to corresponding imines using TiO 2 as the photocatalyst. [10] Lin et al found that some doped metal-organic frameworks showed photocatalytic activity for the oxidation. Therefore, the development of visible-light-driven catalysts for aerobic oxidation of amines remains a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Among the mechanistic scenarios considered for the observed epimerization process, a dehydroamination–hydroamination pathway seemed most plausible and was supported by the careful isolation of a dehydroamination intermediate ( Boc‐18 b , Scheme 3 a‐iii). Finally, based on previously reported examples, we also considered the possibility of a dehydroxymethylation reaction to access deoxyquinine ( 18 ) from primary alcohol 17 directly (Scheme b). In this context, while the rhodium catalytic conditions recently disclosed by Dong and co‐workers were ineffective for model substrate 17 b , preliminary studies demonstrated Pd II catalysis under conditions reported by Maiti and co‐workers could afford product 17 c (43 %, unoptimized) with its newly formed olefin as a useful diversity‐enabling handle.…”
Section: Figurementioning
confidence: 99%